Feasibility Design Study of Long Life BWR with Natural Uranium/Thorium as Fuel Cycle Input - Zaki Su'ud; Rijal Kurniadi; Rida SNM; Zuhair Zuhair (Institut Teknologi Bandung, 2009)
Feasibility design study of Long Life BWR with natural uranium/thorium as fuel cycle input has been performed. The reactor core is divided into 6 equal regions in radial direction. The fresh fuel is first loaded into the most outer region then shifted to the center of the core, and from there shifted to the nearby region in the outward direction. Nitride fuel is employed in the core to get better criticality and conversion/breeding ratio. The results show that uranium fuel combined with low moderating ratio environment is superior to make the system critical.